Predictive Factors in Teachers´ Engagement in Change Processes in Peruvian Public Schools: A Structural Model - Cerviño, Consuelo (2016)
Teachers´ engagement in change processes is closely related to their attitudes and views on education. Therefore, any successful educational change demands that teachers reevaluate their profession, as personal and professional factors are clearly relevant. The goal of this study is to test a predictive statistical model of teacher´s engagement in educational change considering personality factors and self-evaluation. The random and representative sample of Peruvian teachers comprised of 888 subjects. Results show good model fit and a strong predictive power on educational changes. The study confirms that personality and selfconcept are strong predictors on teacher´s engagement with educational change.